1997
DOI: 10.1139/m97-102
|View full text |Cite
|
Sign up to set email alerts
|

The expression of nonagglutinating fimbriae and its role inProteus mirabilisadherence to epithelial cells

Abstract: Proteus mirabilis is a common causative agent of human urinary tract infections, especially in catheterized patients and in those patients with structural abnormalities of the urinary tract. In addition to the production of hemolysin and urease, fimbriae-mediated adherence to uroepithelial cells and kidney epithelium may be essential for virulence of P. mirabilis. A single P. mirabilis strain is capable of expressing several morphologically distinct fimbrial species, which can each be favoured by specific in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…no. 85061107) (Tolson et al, 1997). For the adherence assay, bacteria from an 18 h culture at 37 uC on LB agar were inoculated into 5 ml of LB broth and grown statically at 37 uC for 48 h. Then, bacteria were harvested and resuspended in McCoy's 5a supplemented with 2 mM glutamine and 10 % (v/v) fetal calf serum to 2610 8 c.f.u.…”
Section: Methodsmentioning
confidence: 99%
“…no. 85061107) (Tolson et al, 1997). For the adherence assay, bacteria from an 18 h culture at 37 uC on LB agar were inoculated into 5 ml of LB broth and grown statically at 37 uC for 48 h. Then, bacteria were harvested and resuspended in McCoy's 5a supplemented with 2 mM glutamine and 10 % (v/v) fetal calf serum to 2610 8 c.f.u.…”
Section: Methodsmentioning
confidence: 99%
“…The N-terminal sequence of this fimbrial subunit was confirmed to be identical to the N-terminal sequence from P. mirabilis strain HU1069 of the study reported by Wray et al and not homologous to the N termini of MR/P, ATF, or PMF fimbrial subunits (406). Bacteria expressing NAF adhered strongly to a number of cell lines in vitro, including uroepithelial cells (407) and MDCK (Madin-Darby canine kidney) (5,216) and EJ/28 urinary tract tumor (214) cell lines. Purified NAF from P. mirabilis binds to a number of glycolipids such as asialo-GM1, asialo-GM2, and lactosyl ceramide, as demonstrated by thin-layer chromatography overlay assays and solidphase binding assays (216).…”
Section: Adhesinsmentioning
confidence: 99%
“…We have previously demonstrated that an anti-NAF mAb, NAF.31, was capable of inhibiting P. mirabilis binding to a number of epithelial cell lines (Tolson et al 1997). It was of interest to see if this antibody is also effective in inhibiting NAF binding to the glycolipid receptors.…”
Section: Inhibition Of Naf Binding To Immobilized Asialo-gm1 Asialo-mentioning
confidence: 99%
“…Microtiter wells were coated with LacCer, asialo-GM2, or asialo-GM1 (1 µg per well), and blocked as described above. Anti-P. mirabilis NAF monoclonal antibodies, NAF.31, generated in our laboratory (Tolson et al 1997), were employed in these assays. Purified NAF.31 mAb was premixed with Bt-NAF in PBS containing 1% BSA, and incubated for 30 min prior to addition to precoated wells.…”
Section: Inhibition Of Naf Binding To Immobilized Asialo-gm1 Asialo-mentioning
confidence: 99%
See 1 more Smart Citation